Efficacy of left bundle branch area pacing in patients with indication for cardiac resynchronization therapy. (14th October 2021) - Elvira Ruiz, G; Penafiel-Verdu, P; Munoz-Esparza, C; Martinez-Sanchez, J; Sanchez-Munoz, J J; Garcia-Almagro, F; Salar-Alcaraz, M; Pastor-Perez, F J; Fernandez-Villa, N; Veas-Porlan, M; Martinez-Herrera, M; Vazquez-Andres, D J; et al.
Abstract: Background: Cardiac resynchronization therapy (CRT) with biventricular pacing has demonstrated clinical benefits in heart failure patients with left bundle branch block (LBBB) and ventricular dysfunction. Left bundle branch area pacing (LBBAP) results in a relatively short QRS duration (QRSd) with fast left ventricular activation and could be considered as an alternative to conventional CRT. Purpose: The aim of the present study was to evaluate the feasibility and outcomes of LBBAP in patients with indications for CRT. Methods: Consecutive patients with indications for CRT were included. LBBAP was performed via transventricular septal approach (1–3). We aimed to achieve a paced QRS with right bundle branch conduction delay morphology, a stimulus to peak left ventricular activation time (S-LVAT) <100ms and/or a QRSd ≤130ms. AV delay programming was individualized in patients in sinus rhythm, taking consideration of the AV conduction, programming the one that generated the shortest QRSd at rest. Rate adaptive AV was also activated in these patients. Pacing electrical and echocardiographic parameters were recorded at baseline and during follow-up. Results: LBBAP was achieved in 19 of 21 (90.5%) patients with indication for CRT. Indications were heart failure with LBBB and left ventricular ejection fraction (LVEF) ≤35% in 8 (42%), AV node ablation or AV block with LVEF <50% and high expected RV pacing burden in 9 (47%), 1 pacing-induced cardiomyopathy and 1 patient with biventricular pacemaker malfunction (high LV capture threshold). The mean follow-up was 4.6±1.7 months and the percentage of ventricular pacing was 93.4±13.9%. There were no device-related complications during this period. LBBA capture threshold was 0.6±0.3V at 0.4ms at the implantation, and remained stable (0.7±0.1 V, p=0.17). The lead impedance and R-wave amplitude at implantation were 636±106 ohms and 13.4±6.8 mV, and 541±88 ohms and 13.0±5.1 mV during the follow-up (p<0.001 and p=0.27, respectively). Mean S-LVAT was 85.5±13.9 ms, and mean QRSd was 122±9 ms, that remained stable during follow-up (122 vs 124 ms, p=0.21). In patients with LBBB, a significant narrowing of paced QRSd was achieved (160.9±16.7 vs. 123.9±9.7 ms, p<0.001). Mean LVEF increased by 15.9%, from 35.4±8.9% at baseline to 51.3±9.8% at follow-up (p<0.001) in the overall population, and 14.5% (from 32.7±4.8% to 47.2±10.7%, p=0.001) in patients with LBBB. After one month, estimated time for elective replacement was 11.9±0.4 years. Conclusions: LBBPA was successfully achieved in 90.5% of the patients with indication for CRT, with good and stable pacing electrical parameters, long estimated battery longevity and relatively narrow QRS, and was associated with improvement in cardiac function. LBBAP may be considered as a first-line option for patients with indications for CRT. Funding Acknowledgement: Type of funding sources: None.